2013
DOI: 10.5152/balkanmedj.2013.8475
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Cysts of the Maxillary Sinus in Solid Organ Transplant Population: Computerised Tomography Follow-Up Results

Abstract: Background: The clinical significance of maxillary sinus mucosal cysts in liver and kidney transplant recipients remains unclear.Aim: To investigate the course of maxillary mucosal cysts in liver and kidney transplantation patients. Study Design: Retrospective clinical studyMethods: Paranasal sinus computed tomography scans of 169 renal and 43 hepatic transplant recipients were reviewed. The incidence, size and growth characteristics of maxillary mucosal cysts in the renal and hepatic transplant population wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…According to Aydin et al, the incidence of MSMC did not differ between the cohort of organ recipients and general population [46]. Nevertheless, the authors found higher tendency of MSMC enlargement in RTRs than in healthy population [46].…”
Section: Sinonasal Dysfunctionsmentioning
confidence: 91%
See 3 more Smart Citations
“…According to Aydin et al, the incidence of MSMC did not differ between the cohort of organ recipients and general population [46]. Nevertheless, the authors found higher tendency of MSMC enlargement in RTRs than in healthy population [46].…”
Section: Sinonasal Dysfunctionsmentioning
confidence: 91%
“…Nevertheless, the authors found higher tendency of MSMC enlargement in RTRs than in healthy population [46]. They concluded that it could have been a result of immunosuppressive therapy and higher frequency of upper respiratory tract infections in organ recipients [46]. This observation should be analyzed with caution because of the lack of other studies on this subject.…”
Section: Sinonasal Dysfunctionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Routine paranasal sinus CT scans are not feasible in patients scheduled for organ transplant according to the high rate of false-positive results; therefore, we did not perform radiological imaging methods in every transplant candidate. This means that our patients might already have maxillary mucosal cysts before transplantation (10).…”
Section: Discussionmentioning
confidence: 99%